2015
DOI: 10.1016/j.cub.2014.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Motor Cortices Differentially Support the Translation of Foreign Language Words

Abstract: At present, it is largely unclear how the human brain optimally learns foreign languages. We investigated teaching strategies that utilize complementary information ("enrichment"), such as pictures or gestures, to optimize vocabulary learning outcome. We found that learning while performing gestures was more efficient than the common practice of learning with pictures and that both enrichment strategies were better than learning without enrichment ("verbal learning"). We tested the prediction of an influential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
7
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 29 publications
9
138
7
3
Order By: Relevance
“…In the discussion, words learned with gestures were described, for example, as being more "sticky" and that thinking or seeing the gesture made the word "pop into your head." Although these student perceptions cannot be definitively supported within the current action research design, they lend support to the experimental research cited previously, which showed that words learned with gestures are recalled better, especially in the long term (Macedonia & Klimesch, 2014;Mayer et al, 2015;Tellier, 2008), and are in line with theoretical frameworks that posit learning benefits when perceptual and motor cues are used, such as Dual Coding Theory (Paivio, 1986) and Cognitive Load Theory (Sweller et al, 2011).…”
Section: Student Perceptionssupporting
confidence: 77%
See 2 more Smart Citations
“…In the discussion, words learned with gestures were described, for example, as being more "sticky" and that thinking or seeing the gesture made the word "pop into your head." Although these student perceptions cannot be definitively supported within the current action research design, they lend support to the experimental research cited previously, which showed that words learned with gestures are recalled better, especially in the long term (Macedonia & Klimesch, 2014;Mayer et al, 2015;Tellier, 2008), and are in line with theoretical frameworks that posit learning benefits when perceptual and motor cues are used, such as Dual Coding Theory (Paivio, 1986) and Cognitive Load Theory (Sweller et al, 2011).…”
Section: Student Perceptionssupporting
confidence: 77%
“…Although there are limits to when such gestures can be used-for example, gestures for similar concepts can overlap and gestures alone cannot illustrate the meanings of abstract words-studies have found that words learned in this VOLUmE 34, iSSUE 1,2016 manner are recalled better (Kelly, McDevitt, & Esch, 2009;Morett, 2014) and used more in writing (Macedonia & Knösche, 2011) than are words learned via L1 translations, potentially because adding gestures leaves deeper memory traces (Kelly et al, 2009). Learner involvement appears to be another factor: studies have shown that gestures lead to better word recall than do other visual supports, such as pictures, especially when learners actively repeat both word and gesture (Mayer, Yildiz, Macedonia, & von Kriegstein, 2015;Tellier, 2008).…”
Section: Gestures In L2 Vocabulary Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, handedness influences whether left or right motor cortex becomes active during action word processing (Willems et al 2010), proficiency in first or second language influences the extent of such activation (Vukovic and Shtyrov 2014), as does professional and motoric experience, such as in experts vs. novices (Del et al 2010;Behmer and Jantzen 2011). Learning context also plays a role, and activity in visual and motor cortices predicts superior performance even months after enriched (multi-sensory) word learning, but not if words are learned by passive reading or translation (Mayer et al 2015). Finally, more research is needed on how TMS affects semantically shallow tasks, in which performance does not depend on conscious retrieval of word meaning.…”
Section: Discussionmentioning
confidence: 99%
“…They use Event-related Potentials (ERPs) and functional Magnetic Resonance Imaging (fMRI) techniques to explore the complex cognitive and translation process of learners. Mayer, et al (2015) investigate the teaching effects of two strategies: picture teaching and body language teaching in vocabulary translation learning. They use fMRI to decode the visual and cortical movements of the brain as students listen and translate.…”
Section: Theory and Practice In Language Studies 661mentioning
confidence: 99%